(untitled) (International Journal of Engineering and Computer Science, 2018)
Building software architectures from a set of requirements has been an area of research where programmers, architects and software engineers spend a lot of time using their expertise in resolving peculiar problems of mapping requirements to architectures. Some of these problems are directly associated with the ambiguity, incompleteness and inconsistency of requirements which draw a wide gap between the informal and formal specification of these requirements. The main objective here is to reconcile the mismatch in-between these domains by providing a systematic mapping technique. This paper presents a tool from which requirements are read from user in natural language or file and generated into words whereby the user makes some selections and maps the selected words directly to components architecture. Based on the design of this tool, human heuristic is used in the selection of the words. Unlike components, connectors are set as static. Partial architecture of requirements is drawn incrementally until complete system architecture is constructed